1974
DOI: 10.1113/jphysiol.1974.sp010522
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on retinal ganglion cell response and e.r.g. of goldfish

Abstract: To verify whether a relationship exists between temperature and spectral coding, as has been suggested on the basis of behavioural studies, photopic e.r.g. action spectra were recorded and the spectral coding of ganglion cells were determined as a function of temperature.8. The results point to a temperature invariance of both the photopic e.r.g. action spectra and the colour coding of ganglion cell responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…The results suggest that glutamate may modulate the activity of INL neurons at higher frequencies, but cannot drive the RGC firing rates at those higher frequencies. We speculate that this difference between gSR and gLFP response frequencies may be due to the relatively low temperature (22 °C) at which this study was conducted because previous work has shown that the latencies of LFP responses are less affected by shifts in temperature than spike rate responses33. Extrapolating our data to body temperature (37 °C) using the Q10 values reported by Schellart et al 33,.…”
Section: Resultsmentioning
confidence: 83%
“…The results suggest that glutamate may modulate the activity of INL neurons at higher frequencies, but cannot drive the RGC firing rates at those higher frequencies. We speculate that this difference between gSR and gLFP response frequencies may be due to the relatively low temperature (22 °C) at which this study was conducted because previous work has shown that the latencies of LFP responses are less affected by shifts in temperature than spike rate responses33. Extrapolating our data to body temperature (37 °C) using the Q10 values reported by Schellart et al 33,.…”
Section: Resultsmentioning
confidence: 83%
“…The results suggest that glutamate may modulate the activity of INL neurons at higher frequencies, but cannot drive the RGC firing rates at those higher frequencies. We speculate that this difference between gSR and gLFP response frequencies may be due to the relatively low temperature (22°C) at which this study was conducted because previous work has shown that the latencies of LFP responses are less affected by shifts in temperature than spike rate responses 29 . Extrapolating our data to body temperature (37°C) using the Q10 values reported by Schellart et al .…”
Section: Resultsmentioning
confidence: 87%
“…Extrapolating our data to body temperature (37°C) using the Q10 values reported by Schellart et al . 29 , we predict that gSR temporal resolutions as high as 14 Hz may be achievable.…”
Section: Resultsmentioning
confidence: 90%
“…The responses of goldfish cones were recorded at room temperature (20°C) whereas the responses of macaque horizontal cells were recorded at 36°C (Dacey & Lee, 1994). Given a Q 10 between 2 and 4 (Schellart et al 1974), this temperature difference can account for the differences in time constants. The close correspondence of the other parameters between the goldfish and macaque cones may reflect the high level of conservation in the phototransduction machinery between these species.…”
Section: Discussionmentioning
confidence: 99%